2017
DOI: 10.1161/hypertensionaha.117.09086
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Reduction of Blood Pressure With Baroreceptor Activation Therapy

Abstract: Baroreflex activation therapy (BAT) is a novel way of treating hypertensive patients who respond inadequately to medical therapy. After short-term human studies had shown that electric stimulation of the carotid sinus can lower blood pressure, 1,2 the DEBuT-HT study (Device-Based Therapy of Hypertension) demonstrated a substantial and sustained reduction in blood pressure over a period of 3 months in treatment-resistant hypertensive patients.3 Subsequently, the Rheos Pivotal Trial evaluated the effect of BAT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 26 publications
2
70
0
6
Order By: Relevance
“…Recently, baroreflex activation therapy (BAT), which activates baroreceptors in the carotid sinus by electrostimulation induced by an implantable device (Rheos System, CVRx Inc., Minneapolis, MN, USA), inhibits sympathetic nerve activity, and eventually decreases blood pressure, has drawn attention as a nondrug treatment. BAT was shown to decrease blood pressure 39,40) and BPV 41) in patients with resistant hypertension. BAT also improved BRS and muscle sympathetic nerve activity in patients with chronic heart failure with elevated sympathetic nerve activity.…”
Section: Baroreflex Sensitivity and Variability Of Blood Pressurementioning
confidence: 97%
“…Recently, baroreflex activation therapy (BAT), which activates baroreceptors in the carotid sinus by electrostimulation induced by an implantable device (Rheos System, CVRx Inc., Minneapolis, MN, USA), inhibits sympathetic nerve activity, and eventually decreases blood pressure, has drawn attention as a nondrug treatment. BAT was shown to decrease blood pressure 39,40) and BPV 41) in patients with resistant hypertension. BAT also improved BRS and muscle sympathetic nerve activity in patients with chronic heart failure with elevated sympathetic nerve activity.…”
Section: Baroreflex Sensitivity and Variability Of Blood Pressurementioning
confidence: 97%
“…These include baroreceptor activation therapy,17, 18, 19 renal denervation,7, 20 arteriovenous shunting,10, 21 carotid body resection or denervation,12, 22 and mechanical stimulation of the baroreceptors 23. Prior review articles have provided overviews and comparisons of these different approaches and will not be repeated here,24, 25 other than to say that treatment of isolated systolic hypertension (ie, patients with office diastolic blood pressure <90 mm Hg), which is characterized by increased vascular stiffness, has proved to be particularly challenging for some of these approaches, with such patients excluded from the recently complete SPYRAL HTN‐OFF MED study 19, 26. It is therefore noteworthy that 78% of patients in the present study had isolated systolic hypertension with an excellent response rate.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical implication. In addition to a possible application to the LVAD therapy, the issue of baroreflex responses to pulsatile blood pressure signals at the carotid sinus is especially important in the context of the advent of nonpharmacological therapies for hypertension such as the electrical baroreflex activation (6,28). A previous study has shown that a burstmode stimulation is more effective than a constant-mode stimulation in reducing AP during an electrical stimulation of the myelinated fibers of the aortic depressor nerve (7).…”
Section: Discussionmentioning
confidence: 99%